Improving Reading Comprehension Skills through Reading Strategies Used by a Group of Foreign Language Learners - Nancy Gómez Torres; Jhon Jairo Ávila Constain (Asociación Colombiana de Profesores de Ingles, 2009)
A research study included the examination and implementation of a variety of strategies in order to improve students' reading comprehension skills in a foreign language. Reading is the process of identification, interpretation and perception of written or printed material. Comprehension is the understanding of the meaning of written material and involves the conscious strategies that lead to understanding. The reading strategies are conscious techniques or unconscious processes employed by readers in their attempt to make sense of the written text (Barnett as cited by Gascoigne, 2005). Thus, the main goal of this piece of research was to implement some reading strategies in 2 elementary courses in EFL in order to obtain better results in the middle and long term in class and on ECAES, MICHIGAN, MELICET and PET tests.